Development of Learning Paths on Opportunities Based on Realistic Mathematical Education in Class VIII SMP - Beta Indo Putra; IMade Arnawa; Edwin Musdi; EZ Jamaan (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this research is to design a learning flow for the topic of statistics for class VIII SMP based on Realistic Mathematics Education (RME), implemented through HLT, valid and practical Teacher's Books and Student's Books that can improve students' problem solving abilities. The method used in this study is to combine the Plomp research design model with the Gravemeijer Cobb model, which consists of 3 phases, namely the preliminary research phase (preparing for the experiment), the development phase (development or prototyping phase/design experiment) and the development phase (development or prototyping phase/design experiment). assessment (retrospective assessment/analysis stage). From this research, the flow of learning statistics topics for class VIII SMP is generated. The resulting learning design also meets practical criteria with the characteristics of helping students understand material concepts and making it easier to develop mathematical problem solving skills.